Hill to Plain: Causes and Impacts of Internal Migration of Indigenous Peoples in Bangladesh - Akter Akhy, Asma; Chakma, Basu Mittra (Scientific Research Publishing, 2015)
Various factors are related in internal migration of indigenous peoples from their ancestral places, that is hill, to the plain areas. This article aims to find out the pull and push factors of the indigenous migration. The study has been conducted in Chittagong Export Processing Zone at Chittagong, Bangladesh. The major finding of the study is that indigenous peoples are greatly migrated to plain places for economic reason voluntarily. It also indicates that among 14 indigenous groups living in the Chittagong Hill Tracts (CHT), mainly Chakma people have been migrated in large volume. It finds that women are clearly ahead than their counterparts in migrating to the plain areas. The migrant’s traditional culture
Keywords: Chittagong Hill Tracts; Internal Migration; Indigenous Peoples; Hill to Plain